The minimum process for canned tropical mushroom (Volvariella volvacea ex. Bull. Singer) using still retort - Bautista, Virginia R.; Alabastro, Estrella F. (1974)
Thermal death time, heat penetration, sensory evalustion and cut-out tests were performed to determine the minimum process for canned "button" mushroom (Volvariella volvacea) in 2 percent brine. Thermal death time of P.A. 3679 heated in mushroom puree gave Dr. value of 1.6 and z value of 18.5. Heat penetration parameters obtained were jch = 1.00; jcc = 3.00; fh = 5.2; fc = 6.9 at Tr = 250F and Tih = 140F. Based on these data, the calculated process for the product packed in 307 x 409 can is 14 minutes at 250F or 34 minutes at 240F. Routine cut-out examination of the samples stored at 98F at one indicated a sound product. Sensory evaluation resulted in preference for the sample processed at 250F for 14 minutes, flavorwise. These experimental samples, in turn, were preferred over an imported commercial brand from Taiwan which served as the reference sample.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Mushrooms -- Preservation